A THREE-DIMENSIONAL EVALUATION OF THE EFFECTS OF DIFFERENT INCISOR INTRUSION MECHANICS TO THE PERMANENT MAXILLARY FIRST MOLAR TEETH BY USING CONE BEAM COMPUTED TOMOGRAPHY - Fatih Kahraman; Nihat Kılıç; İlhan Metin Dağsuyu (Cumhuriyet University, 2017)
Objective: The present study aims to evaluate the impacts of the upper incisor teeth intrusion in deepbite patients by two different techniques to the permanent maxillary first molar tooth using the three-dimensional cephalometric analysis in the individuals. Materials and Methods: The population of this study consists of 34 patients with >4 mm overbite and a ≥2 mm gummy smile during post-pubertal period. Patients who underwent intrusion of upper incisor teeth were randomized to receive Connecticut intrusion arch (CTA) or miniscrew anchorage intrusion system (MAIS) to compare the impacts on permanent maxillary first molar teeth. Cone Beam Computed Tomography (CBCT) data obtained before (T1) and after (T2) intrusion were evaluated through three-dimensional (3D) cephalometric analysis. Intragroup assessment of treatment-related variables were performed via "t-test in dependent samples" and intergroup comparisons were assessed by "t-test in independent samples".Results: In patients who underwent intrusion of upper incisors, permanent maxillary first molar teeth became deviated distally (1.48 mm/7.63 degree) only in CTA group, a statistically significant difference was found between two groups (p<0.05). The distance between resistance centers of maxillary first molar teeth was only increased in CTA group (0.31 mm), which also statistically differed from MAIS group. Conclusion: CTA and MAIS techniques resulted in similar intrusive effects overall at the end of the treatment. While MAIS is recommended when anchorage from posterior region is not desired in patients with deep overbite, we believe that CTA may serve a suitable treatment alternative where miniscrew technique could not be performed.